Muscle activation during swimming exergame - Soltani, P.; Figueiredo, P.; Fernandes, R. J.; Fonseca, P.; Vilas-Boas, J. P. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Swimming exergames may provide low-cost opportunities for teaching and practicing real swimming. The purpose of this study was to characterise the muscle activation during a swimming exergame. Ten healthy subjects played four swimming techniques using 'Michael Phelps: Push the Limit' exergame by standing in front of Xbox360 and Kinect. Muscle activation for Biceps Brachia/is (Bi), Triceps Brachia/is (Tri), Latissimus Dorsi (LD), Upper Trapezius (UT) and Erector Spinae (ES) was recorded on dominant upper limb using a wireless EMG Trigno system (Delsys lnc, USA) at sampling rate of 2000Hz, and was normalised to the maximal voluntary isometric contraction. EMG recordings were divided into a low intensity phase and a second phase of fast swimming. Both phases were evaluated in terms of EMG morphology (average peak value). Preliminary results show high contributions of UT. Particularly high activation values were obtained for back crawl, where more expressive shoulder flexion is required. Lower contributions of other muscles might be related to lack of sufficient mechanical resistance. Prevalence of the activity of the Tri relatively to the Bi was also observed, as expected, considering the final acceleration of the lower part of the arm in all swimming techniques. Due to great activity of UT, proper warm up and the use of strategies to transfer the muscle activity are advisable. More results of this ongoing project will be available in the future.